Exploring Innovative Resource Allocation and Service Delivery Performance in Developing Countries (Journal of Governance and Development (JGD), 2014)
New governance paradigm in managing public resources needs to be given signiï¬ cant review while looking at alternatives in improving public service delivery. It implies that theories and practices of public administration, new public management, public value management or good governance need to be redesigned to embrace the public sector, private sector and the community. The relationship between resource allocation and service delivery performance is best viewed from view-lens of innovative governance. Innovative governance must be seen from the view point of integrating the public sector, market and community to deliver systematic public goods and services. This paper examines the relationship between innovative resource allocation and service delivery performance in developing countries. This paper uncovers various new models of allocative resource innovation taken from case studies reported in ten years of World Bank reports. The cases suggested that many countries are introducing several transformational programs, adopting open search strategies, and embarking on economic transformational agenda, which involve the use of a wide range of public private partnership strategy, private ï¬ nance initiatives, performance-based management and other actors/sources to achieve the governmental programs. However, the impact of innovative governance on resource allocation and service delivery performance is often felt in developed countries, but the reverse is the case in the developing countries.